Visions of Britain & Ireland [videorecording (DVD)] - Toperoff, Sam; Toperoff, Sam; Toperoff, Sam; Toperoff, Sam; Hammond, Roy A.; Hammond, Roy A.; Barchiesi, Franca; Wallace, James, 1961-; Donnelly, Terry; Davies, Geraint Wyn, 1957-; Brygider, Roman; Brygider, Roman; et al. (WLIW21, 2016)
A visual itinerary, an emotional visit to a family's homeland, a souvenir of the trip of a lifetime, or the virtual realization of a fantasy vacation - whatever the inspiration, one thing's certain - locations like this won't be seen any other way.